Efektivitas Metode Numbered Head Together dalam Meningkatkan Prestasi Akademik pada Mata Pelajaran Fikih Kelas VIII (Studi Kasus MTs Plus Al Munawwaroh Diwek Jombang) - Baihaqi, Akhmad; Shobirin, Mochammad Syafiuddin; Akbar, Irwan Ahmad (ARZUSIN, 2026)
Although cooperative learning has received attention in various Islamic education studies, research specifically discussing the effectiveness of the Numbered Head Together (NHT) method in improving academic achievement in Fiqh at the madrasah tsanawiyah level remains limited. This study aims to describe the implementation of the NHT method and analyze its effectiveness in improving the academic achievement of Grade VIII students in Fiqh. This study used a descriptive qualitative approach with a case study design, involving teachers, the principal, and Grade VIII students of MTs Plus Al Munawwaroh Diwek Jombang as research subjects and informants selected purposively. Data were collected through participant observation, semi-structured interviews, and documentation, and were then analyzed through data reduction, data display, and conclusion drawing with source triangulation validation. The results show that the implementation of the NHT method was effective in accordance with the learning syntax and was able to create an active and interactive learning atmosphere. This method increased student participation from 30–40% to 85–90%, improved conceptual understanding of abstract material such as zakat, and developed soft skills in the form of cooperation and responsibility. The students’ average score increased from 72 to 82, accompanied by a decrease in the number of students requiring remedial instruction to 3–4 students per class. This finding contributes to the development of cooperative learning theory and broadens understanding of learning method innovation in Islamic Religious Education. The conclusion of this study emphasizes that individual accountability, peer tutoring, and positive interdependence play an important role in cooperative-based Fiqh learning. The practical implications of this study indicate that teachers and Islamic educational institutions can adopt the NHT method in a structured manner to improve student participation, conceptual understanding, and academic achievement.